1998
DOI: 10.1002/(sici)1096-9861(19980112)390:2<278::aid-cne10>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of type II calcium/calmodulin-dependent protein kinase isoforms and glutamate receptors in normal and visually deprived lateral geniculate nucleus of monkeys

Abstract: In situ hybridization histochemistry and immunocytochemistry were used to map distributions of cells expressing mRNAs encoding alpha, beta, gamma, and delta isoforms of type II calcium/calmodulin-dependent protein kinase (CaMKII), alpha-amino-3-hydroxy-5-methyl-4-isoxazoleproprionate (AMPA)/ kainate receptor subunits, (GluR1-7), and N-methyl-D-aspartate (NMDA) receptor subunits, NR1 and NR2A-D, or stained by subunit-specific immunocytochemistry in the dorsal lateral geniculate nuclei of macaque monkeys. Relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 122 publications
(136 reference statements)
1
14
0
Order By: Relevance
“…A further, relevant observation is that when they do not kill cells, persistent decreases in neuronal excitability are known to be associated with changes in the sensitivity and subunit composition of AMPA and NMDA receptors (Tighilet et al, 1998;Alvarez et al, 2000;Brown et al, 2004). And indeed, the present experiments showed that unilateral LS lesions caused 18% of calbindin-positive cells and 24% of parvalbumin-positive cells in area 18 of both hemispheres to decrease their expression of GluR2 and 2/3 below levels detectable with immunohistochemistry.…”
Section: Unilateral Ls Lesions Cause Bilateral Decreases In Ampa Recesupporting
confidence: 57%
“…A further, relevant observation is that when they do not kill cells, persistent decreases in neuronal excitability are known to be associated with changes in the sensitivity and subunit composition of AMPA and NMDA receptors (Tighilet et al, 1998;Alvarez et al, 2000;Brown et al, 2004). And indeed, the present experiments showed that unilateral LS lesions caused 18% of calbindin-positive cells and 24% of parvalbumin-positive cells in area 18 of both hemispheres to decrease their expression of GluR2 and 2/3 below levels detectable with immunohistochemistry.…”
Section: Unilateral Ls Lesions Cause Bilateral Decreases In Ampa Recesupporting
confidence: 57%
“…For example, distinct populations of inhibitory neurons can be distinguished by parvalbumin, calbindin and nitric oxide synthase (NOS) immunoreactivity [68], [69] and robust expression of αCaMKII is present in excitatory neurons [70], [71], [72], [73], [74]. In stage 47 Xenopus tadpoles, we found that strongly GABA and αCaMKII immunoreactive sub-populations were mutually non-overlapping in the optic tectum (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Silver grain analysis of emulsion dipped cerebellar slides confirmed that granule and Purkinje neurons in cerebellum are also labeled. The XIST in situ hybridization histochemistry was repeated with two different methods (Gee et al, 1983;Tighilet et al, 1998) and gave similar conclusions.…”
Section: In Situ Hybridization Histochemistrymentioning
confidence: 84%
“…Since some genes of interest did not differ sufficiently for optimal riboprobe design, oligonucleotide probes were synthesized for h-clone 23599 (NCBI Genbank accession #U79247, nucleotide coding region 1091-1106), h-USP9Y (AF000986, 1384-1412), h-RSP4Y (M58459), and h-DBY (AF000984, 3125-3157). 35 Sor 33 P-labeled sense and antisense oligo-or riboprobes were prepared and hybridized to sections from the DLPFC, anterior cingulate cortex, and cerebellum using previously published methods (Meador-Woodruff et al, 1989;Tighilet et al, 1998). Hybridized sections were exposed to Kodak XAR film for 2-4 weeks and after development of the film, the sections were dipped in Kodak autoradiographic emulsion and exposed for further 2-4 weeks, as described in the published methods.…”
Section: In Situ Hybridization Histochemistrymentioning
confidence: 99%